1998
DOI: 10.1111/j.1745-3984.1998.tb00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Projecting to the NAEP Scale: Results from the North Carolina End‐of‐Grade Testing Program

Abstract: Data from the North Carolina End‐of‐Grade test of eighth‐grade mathematics are used to estimate the achievement results on the scale of the National Assessment of Educational Progress (NAEP) Trial State Assessment. Linear regression models are used to develop projection equations to predict state NAEP results in the future, and the results of such predictions are compared with those obtained in the 1996 administration of NAEP Standard errors of the parameter estimates are obtained using a bootstrap resampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Although not reported in the technical manual, evidence of concurrent and predictive validity for the EOG Mathematics Tests was provided in several additional studies. Williams, Rosa, McLeod, Thissen, and Sanford (1998) linked a shortened version of the EOG Mathematics Tests (1st edition) with NAEP mathematics scores. In a summary of this study, Thissen (2007) reported that the EOG Mathematics Tests-NAEP correlation was .73.…”
Section: Characteristicmentioning
confidence: 99%
“…Although not reported in the technical manual, evidence of concurrent and predictive validity for the EOG Mathematics Tests was provided in several additional studies. Williams, Rosa, McLeod, Thissen, and Sanford (1998) linked a shortened version of the EOG Mathematics Tests (1st edition) with NAEP mathematics scores. In a summary of this study, Thissen (2007) reported that the EOG Mathematics Tests-NAEP correlation was .73.…”
Section: Characteristicmentioning
confidence: 99%
“…Our analysis shows that linear regression gives an appropriate linking function (viewed as a BLP approximation to the posterior expectation) but that the proper residual standard deviation is not that given by the usual regression results. This justifies the use of multiple regression to link tests in studies such as Pashley and Phillips (1993) and Williams et al (1995).…”
Section: Discussionmentioning
confidence: 92%
“…Our analysis shows that linear regression gives an appropriate linking function (viewed as a BLP approximation to the posterior expectation) but that the proper residual standard deviation is not that given by the usual regression results. This justifies the use of multiple regression to link tests in studies such as Pashley and Phillips (1993) and Williams, Billeaud, Davis, Thissen, and Sanford (1995).…”
Section: Discussionmentioning
confidence: 99%